Грустничное варенье: [роман : 16+] / Елена Вернер - Вернер Елена (Верю, надеюсь, люблю, 2015)
Экземпляры: аб (20151111) / Инвентарный номер: 059648 / Цена: 187.00 / Авт.знак: В 35 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6